The socialities of everyday urban walking and the "right to the city' - Middleton, J (SAGE Publications, 2016)
This paper explores the socialities of everyday urban walking. The paper begins from the starting contention that a wide range of social and cultural theory, urban planning and transport literatures position walking as a practice that unproblematically encourages ‘social mixing’, ‘community cohesion’ and ‘social interaction’. Through the analysis of in-depth interview and diary data from research on urban walking in London, this paper engages with a series of underexamined questions. What, for example, is the nature of social interactions on foot? Who are they with, what initiates them and how do they unfold? How do these interactions relate to how we understand the relationship between walking and urban space? Attention is drawn to verbal and non-verbal interactions of strangers as they walk and to the significance of the practical accomplishment of walking together. However, an examination of the discursive organisation of diary and interview data extends existing work concerning the practical organisation of everyday pedestrian mobilities by considering the significance of participants’ accounts of their walking experiences. This analytic move foregrounds a counterposition to dominant discourses surrounding everyday walking practices that is situated in the context of broader concerns with everyday urban politics and the ‘right to the city’. This approach contributes to a clearer engagement with the socialities of urban walking whilst raising important questions concerning the ways in which particular walking discourses inform urban scholarship. The paper concludes that in the promotion of walking as a form of low-carbon active travel greater account should be taken of pedestrian encounters.